Understanding the disruptive business model innovation of E-business microcredit: a comparative case study in China. Issue 7 (3rd July 2018) - Zhang, Wenyao; Daim, Tugrul; Zhang, Qingpu
ABSTRACT: This paper uses an in-depth case study approach to compare and analyze e-business microcredit firms and traditional bank business models in China, employing a business model template redefined as an analytical tool. The results suggest that the EMF business model has typical disruptive innovation characteristics, shedding new light on the definition and criteria of disruptive business model innovation as little research has done on its systematic analysis. This study also presents a holistic conceptual framework for four triggers constituting their business model difference, inclusive of non-mainstream customer positioning, inclusive platform-based infrastructure, platform-based leveraged capability, and user experience-centered value proposition.